Effects of Child-Care Programs on Women's Work Effort - Heckman, James J. (Journal of Political Economy, 1974)
In recent years, Congress has considered a variety of work-subsidy programs designed to encourage work among welfare recipients. Many of these programs would subsidize individuals only if they work some minimum number of hours. Commonly used techniques cannot give direct answers to relevant policy questions since a tied offer is involved, and hence the offer cannot be treated as a simple wage change. The essence of the problem involves utility comparisons between two or more discrete alternatives. Such comparisons inherently require information about consumer preferences in a way not easily obtained from ordinary labor-supply functions. To make such comparisons, I present a method for directly estimating consumer indifference surfaces between money income and nonmarket time. Once these surfaces are determined, they can be used to compare a variety of alternative programs to investigate whether or not there is scope for Pareto-optimal redistribution of income transfers and time, improving the general level of welfare of the community at large without reducing the welfare of individuals receiving income transfers. Knowledge of these indifference surfaces allows us to estimate reservation wages to estimate the value of nonworking-women's time (Gronau 1973), laborforce participation functions, hours-of-work functions, and welfare losses due to income tax programs (Harberger 1964). I demonstrate that direct estimation of indifference surfaces allows us, at least in principle, to relax